Direct Detection of Tissue-Resident Bacteria and Chronic Inflammation in the Bladder Wall of Postmenopausal Women with Recurrent Urinary Tract Infection. Issue 21 (4th October 2019) - De Nisco, Nicole J.; Neugent, Michael; Mull, Jason; Chen, Luming; Kuprasertkul, Amy; de Souza Santos, Marcela; Palmer, Kelli L.; Zimmern, Philippe; Orth, Kim
Abstract: Urinary tract infections (UTIs) are the most commonly reported infections in adult women and have high rates of recurrence, especially in postmenopausal women. Recurrent UTI (RUTI) greatly reduces quality of life, places a significant burden on the healthcare system, and contributes to antimicrobial resistance. Because treatment of RUTI by long-term antibiotic therapy is often ineffective or poorly tolerated in elderly women, new therapies must be developed. The molecular basis of RUTI, especially in postmenopausal women, has remained unclear because modeling RUTI in mice is difficult, and human data are limited. Invasion of the urothelium and induction of host inflammation are hypothesized to be key mechanisms by which bacterial pathogens cause RUTI. To further our understanding of RUTI in humans, we performed a systematic analysis of urine and bladder biopsy samples from postmenopausal women undergoing cystoscopy with fulguration of trigonitis in the advanced management of antibiotic-refractory RUTI. We provide direct evidence that bacteria reside in the bladder wall of postmenopausal RUTI patients and that diverse bacterial species can be isolated from the bladder tissue. Histopathological scoring revealed significant edema and alterations of urothelial architecture in RUTI patient biopsies. Lymphocytes, including plasma B-cells, were detected within the mesenchyme, urothelium, and follicular aggregates in the majority of patients, indicating that the local adaptive immune response is active during human RUTI. These data provide conclusive evidence that bacteria invade the human urothelium and suggest that diverse bacterial species and the adaptive immune response play important roles in RUTI in humans. Graphical Abstract: Unlabelled Image Highlights: Diverse bacterial species isolated from the bladder tissue and urine of postmenopausal RUTI patients Direct detection of bacteria communities of variable size and location within RUTI patient bladder wall Evidence of active plasma B-cell response in the majority postmenopausal RUTI patient biopsies